POLIANITE IN FERROMANGANESE NODULES FROM THE NORTHEASTERN BASIN OF THE PACIFIC OCEAN - Arkhipova L.D.; Gubenkov V.V.; Dudok I.V.; Korsakov O.D.; Marushkin A.I. (My University, 1990)
Investigating the mineral composition of ferromanganese nodules is one of the most important parts of integrated study of these unique objects from the pelagic regions of oceans. The discovery of polianite attracted our attention. Polianite occurs as euhedral crystals, constituting irregular pockets and branching veinlets in pores and cavities of fine-grained ore material in the centers of the nodules (diameter of nodules up to 3 to 5 cm). In isolated places the pockets and veinlets connect to form complex dendritic aggregates. The forms of polianite in the ferromanganese nodules indicate that it was secondary in relation to most of the ore material. Found in a zone of intensive tectonic and magmatic activity the nodules had been subjected to hydrothermal solutions, resulting in the formation of crystalline pyrolusite in cavities and fractures, and alteration of the rocks. The mineralogical, geochemical and stratigraphic features of the sedimentary cover indicate that there were several episodes of volcanotectonic activity: 1) in the middle Miocene; 2) in the early Pliocene; 3) in the late Pliocene and early Pleistocene. It is possible that these episodes correspond to peaks of hydrothermal activity.
Keywords: Miocene; Pliocene; Pleistocene; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Pliocene; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Плиоцен; Кайнозой::Четвертичная::Плейстоцен